Entrepreneurship and Relational Capital in a Levantine Context: Bartolomew Edward Abbott, the "Father of the Levant Company" in Thessaloniki (Eighteenth-Nineteenth Centuries) - Vlami, Despina (The Historical Review/La Revue Historique, 2010)
No abstract